Myosteatosis rather than sarcopenia associates with non‐alcoholic steatohepatitis in non‐alcoholic fatty liver disease preclinical models. Issue 1 (26th November 2020) - Nachit, Maxime; De Rudder, Maxime; Thissen, Jean‐Paul; Schakman, Olivier; Bouzin, Caroline; Horsmans, Yves; Vande Velde, Greetje; Leclercq, Isabelle Anne
Abstract: Background: Non‐alcoholic fatty liver (NAFL) disease (NAFLD) is the most common chronic liver disease in the world. While most subjects have 'inert' NAFL, a subset will progress to non‐alcoholic steatohepatitis (NASH) and its life‐threatening complications. A substantial body of literature supports that a low muscle mass, low strength, and/or muscle fatty infiltration (myosteatosis) are associated with NAFLD severity. Here, we evaluated the muscle compartment in NASH preclinical models to decipher the kinetics of muscle alterations in relation with liver disease progression. Methods: We developed and validated a micro‐computed tomography‐based methodology to prospectively study skeletal muscle mass and density in muscle and liver (i.e. reflecting fatty infiltration) in a high‐throughput and non‐invasive manner in three preclinical NAFLD/NASH rodent models: fat aussie (FOZ) mice fed a high‐fat diet (FOZ HF), wild‐type (WT) mice fed a high‐fat high‐fructose diet (WT HFF), and WT mice fed a high‐fat diet (WT HF). We compared them with WT mice fed a normal diet (WT ND) used as controls. Results: ‐FOZ HF with fibrosing NASH had sarcopenia characterized by a reduced muscle strength when compared with WT HF and WT HFF with early NASH and WT ND controls (165.2 ± 5.2 g vs. 237.4 ± 11.7 g, 256 ± 5.7 g, and 242.9 ± 9.3 g, respectively, P 60; 0.001). Muscle mass or strength was not lower in FOZ HF, WT HF, and WT HFF with early NASH than in controls. Myosteatosis was present in FOZ HF with fibrosing NASH, but also in FOZ HF, WT HF, and WT HFF with early NASH (muscle density = 0.50 ± 0.02, 0.62 ± 0.02, 0.70 ± 0.05, and 0.75 ± 0.03, respectively, with P 60; 0.001 when compared with respective controls). Myosteatosis degree was strongly correlated with NAFLD activity score ( r = −0.87, n = 67, P 60; 0.001). In multivariate analysis, the association between myosteatosis and NASH was independent from homeostatic model assessment of insulin resistance and visceral fat area ( P 60; 0.05). Myosteatosis degree powerfully discriminated NASH from benign NAFL and normal liver (area under the receiver operating characteristic = 0.96, n = 67, P 60; 0.001). Conclusions: Taken together, our data support that there is no sarcopenia in obese mice with early NASH. In contrast, the severity of myosteatosis reflects on hepatocellular damage and inflammation during early NASH development. This observation prompts us to exploit myosteatosis as a novel non‐invasive marker of NASH.